Professional Competence, Library Service Quality and User Satisfaction in Colleges of Education Libraries in Lagos State, Nigeria - Owolabi, Ruth Onajite; Abdullahi, Mostura Adejoke; Agboola , Idayat Odunola; Ogungbade, Aderonke Ayobami (Communicate: Journal of Library and Information Science, 2024)
User satisfaction is a pivotal factor motivating library use, contingent upon competent professionals delivering quality services. Professional competence, encompassing communication and academic qualifications, enables effective library performance. Inadequate library services in colleges of education may hinder user satisfaction. Despite empirical support for user satisfaction with library resources, scant literature addresses professional competence and library service quality's impact on satisfaction in Lagos State's college of education libraries, Nigeria. The study employed a survey design with a population of 12,450 users. A validated questionnaire achieved a 62% response rate, analysed through descriptive and inferential statistics. Results showed significant influence of professional competence on user satisfaction (R2= 0.268, β= 0.518, t = 9.207, p<0.05). To enhance user satisfaction, college library management should assess service quality, employ qualified professionals, and prioritize positive working attitudes and environment. Ultimately, findings highlight the significance of the library environment and staff demeanour in fostering user satisfaction, underscoring the need for skilled professionals and conducive surroundings.